Outcome of Albumin Infusion in Heart Failure Patients - Talukder, Ashaduzzaman; Siraj, Mohamed Mausool; Khondokar, Md Noornabi; Habib, SM Ahsan; Salim, Md Abu; Rahman, Mohammad Walidur; Banerjee, Sajal Krishna; Ahsan, Syed Ali; Hoque, Md Harisul; Rahman, Fazlur (University Heart Journal, 2019)
Background: Heart Failure (HF) is a major public health burden worldwide. Approximately 5 million Americans, 0.4–2% of the general European population and over 23 million people worldwide are living with heart failure. Like few other chronic disease, low serum albumin is common in patients with heart failure (HF). However, very few studies evaluated the outcome of albumin infusion in different stages of HF. Therefore, the objective of this study is to assess the outcome of albumin infusion in heart failure patients. Methods: It was a cross-sectional study. A total of 50 cases of chronic heart failure with reduced ejection fraction and NYHA class III or IV with serum albumin level <2.5g/dl who were admitted in CCUwere selected by purposive sampling, from September 2017 to August 2018. 100ml of 20% albumin was infused and serum albumin was measured after 3 days. Then the patients were divided into two groups, Patients who failed to attain serum albumin of 3g/dl(Group A) or Patients who attained serum albumin of ≥3g/dl (Group B). Analysis and comparison for symptomatic improvement of heart failure by NHYA classification and LVEF was done at 10th day after infusion between group A and B. Result: Among the 50 patients, mean age of patients was 53.64 ± 13.44 years (age range: 26-84 years) with a male-female ratio of 3:2 (60%-male vs 40%- female). Majority patients were previously re-admitted at least two times (40%), 28% were re-admitted once, 16% were re-admitted three times and 4% were re-admitted for four times. Of all, 56% patients presented NYHA class IV and AHA stage D heart failure (56%) and 44% patients presented with NYHA class III and AHA stage C. At day 10 follow up following albumin infusion, overall frequency of following ten days of albumin therapy, in group B, 8 patients (72.7%) among Class III improved to Class I and 3 patients (27.3%) improved to class II. Also, 7 patients (50%), 5 patients (35.7%) and 2 patients (14.3%) among class IV improved to respectively class I, class II and class III. In group A, 3 patients (27.3%) among class III improve to class II and 8 patients (72.7%) remain in class III. Also, 2 patients (14.3%), 5 Patients (35.7%) and 7 patients (50%) among class IV improve to respectively class I, class II and class III. Moreover, statistically significant improvement was noted in ejection fraction of patents irrespective of initial class of heart failure (p<0.001) in group B patients compare to group A (p<0.09). Conclusion: In this study, the improvement of heart failure was more in patients who attained albumin level of ≥3g/dl.Therefore, in can be concluded that albumin infusion improves both subjective and objective improvement of patients with heart failure. University Heart Journal Vol. 15, No. 2, Jul 2019; 47-53